Environmental prediction and innovation - Uddstrom, Michael (New Zealand Science Review, 2011)
​Using weather-related hazards research as a starting point, this paper shows how a research effort focused on natural hazards prediction has developed a capability (EcoConnect) that is now demonstrating benefits far beyond its primary focus. In this regard EcoConnect meets one of the generally accepted definitions of innovation: ‘the successful exploitation of creative ideas within an organisation’. EcoConnect is built on the creative capabilities of a multi-disciplinary team of scientists and ICT specialists and has adopted a partnership-based approach to working with potential endusers. In this way scientists and end-users are exposed to each other’s ideas – leading to both more informed research directions, and, among end-users, a better understanding of the strategic (as well as tactical) potential of new science results. It is also noted that while an ‘innovation system’ is only as good as the quality and quantity of research and technology that underpins it, funding that alone is not sufficient. Investors must be willing to sustain the effort (from basic research to end-user engagement – including iterative innovations arising therefrom) over a long period – especially if the innovation is likely to be disruptive to existing technologies/capabilities.